Variação interindividual no uso de recursos alimentares em populações naturais de mesonauta festivus (heckel, 1840) (cichliformes: cichlidae) em área de várzea na Amazônia central - Albertin Santos, Cândida Juliana (Instituto Nacional de Pesquisas da Amazônia - INPA, 2020)
Individuals within the same population may use different resources simply because they live in different environments or because of differences related to the gender or age classes. However, individuals may also exhibit variation in niche amplitude, even though they belong to the same sex or age class and occurring in the same site and at the same time. This individual variation is called "individual specialization," in which individuals use a subset of resources significantly smaller than that of the population as a whole. Recently it has been shown that individual specialization tends to increase in low latitude environments for different taxonomic groups of animals, including fishes. The cichlid Mesonauta festivus is a tropical fish species that lives in highly diverse communities, with generalist habits and that has a very wide geographic distribution. In this context, individual specialization could occur homogeneously among populations or may vary within a given type of environment according to the local context (resource availability and local ichthyofaunal composition). In this sense, our work investigates the existence of interindividual variation of the cichlid M. festivus in the use of food resources in four localities in a “várzea” floodplain area in the Brazilian Central Amazon: Catalão, Janauari, Iranduba and Pirapora. Morphological analyzes showed that males and females are morphologically similar, differing only in size (females are larger than males). The diet of males and females was different in only two of the localities (Janauari and Iranduba), but there was no relation between morphology and dietary characteristics between the genders. There was no significant correlation between the composition of the diet (verified in the stomach contents) and the isotopic composition of the individuals among the four localities sampled. Mesonauta festivus presented a peculiar situation: it is not a generalist species where all individuals are generalists, but neither is composedof a combination of specialists. The situation varies among the different localities analyzed, and this possibly depends on the context, which involves both the local availability of food items and the composition of the ichthyofauna that shares the environment with M. festivus.
Keywords: Especialização individual; Isótopos estáveis; Mesonauta festivus; Várzea